American Society of Clinical Oncology Statement: Human Papillomavirus Vaccination for Cancer Prevention - Bailey, Howard H; Chuang, Linus T; duPont, Nefertiti C; Eng, Cathy; Foxhall, Lewis E; Merrill, Janette K; Wollins, Dana S; Blanke, Charles D (Journal of clinical oncology, 2016)
American Society of Clinical Oncology (ASCO), the leading medical professional oncology society, is committed to lessening the burden of cancer and as such will promote underused interventions that have the potential to save millions of lives through cancer prevention. As the main providers of cancer care worldwide, our patients, their families, and our communities look to us for guidance regarding all things cancer related, including cancer prevention. Through this statement and accompanying recommendations, ASCO hopes to increase awareness of the tremendous global impact of human papillomavirus (HPV) -caused cancers, refocus the discussion of HPV vaccination on its likely ability to prevent millions of cancer deaths, and increase HPV vaccination uptake via greater involvement of oncology professionals in ensuring accurate public discourse about HPV vaccination and calling for the implementation of concrete strategies to address barriers to vaccine access and acceptance.